2017
DOI: 10.3748/wjg.v23.i15.2685
|View full text |Cite
|
Sign up to set email alerts
|

Changes in human hepatic metabolism in steatosis and cirrhosis

Abstract: AIMTo understand the underlying metabolic changes in human liver disease we have applied nuclear magnetic resonance (NMR) metabolomics analysis to human liver tissue.METHODSWe have carried out pilot study using 1H-NMR to derive metabolomic signatures from human liver from patients with steatosis, nonalcoholic steatohepatitis (NASH) or alcohol-related liver damage (ARLD) to identify species that can predict outcome and discriminate between alcohol and metabolic-induced liver injuries.RESULTSChanges in branched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 51 publications
3
22
0
Order By: Relevance
“…This finding indicates that there was a significant impairment in the TCA cycle due to mitochondrial damage and impaired mitophagy as a mechanism in clearance of damaged mitochondria as demonstrated in our recent study . In supporting our observation in a murine NASH model, elevated succinate levels were reported in NASH patients . At the same time, GPR‐91, a G‐protein‐coupled receptor, was up‐regulated in HSCs of HFCD‐HF/G‐fed mice, HSCs with treatment of succinate in vitro and in human NASH specimens with fibrotic progression, demonstrating a positive correlation between NASH fibrosis severity and GPR‐91 positive staining in liver biopsy specimens.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding indicates that there was a significant impairment in the TCA cycle due to mitochondrial damage and impaired mitophagy as a mechanism in clearance of damaged mitochondria as demonstrated in our recent study . In supporting our observation in a murine NASH model, elevated succinate levels were reported in NASH patients . At the same time, GPR‐91, a G‐protein‐coupled receptor, was up‐regulated in HSCs of HFCD‐HF/G‐fed mice, HSCs with treatment of succinate in vitro and in human NASH specimens with fibrotic progression, demonstrating a positive correlation between NASH fibrosis severity and GPR‐91 positive staining in liver biopsy specimens.…”
Section: Discussionsupporting
confidence: 90%
“…21 In supporting our observation in a murine NASH model, elevated succinate levels were reported in NASH patients. 22 At the same time, GPR-91, a G-protein-coupled receptor, was up-regulated in HSCs of HFCD-HF/G-fed mice, HSCs with treatment of succinate in vitro and in human NASH specimens with fibrotic progression, demonstrating a positive correlation between NASH fibrosis severity and GPR-91 positive staining in liver biopsy specimens. GRP-91 receptor activation elicited phosphorylation of downstream signalling molecules, such as Erk and c-Jun, and production of more extracellular matrices (Procol-I, III, TIMP) and release of fibrogenic cytokines, such as CTGF.…”
Section: Discussionmentioning
confidence: 92%
“…Our study revealed significantly higher lactate levels in livers obtained from patients diagnosed with alcoholic liver disease compared to healthy control livers. Those results are in keeping with the report on higher lactate levels in livers in the course of nonalcoholic steatohepatitis (NASH) and alcohol-related liver damage published by Schofield et al [11].…”
Section: Discussionsupporting
confidence: 92%
“…A UK study used 1 H NMR metabolite profiling to compare livers removed from patients with either LC associated with ALD (5) or with NASH (14) with healthy donor transplant livers (16). Cirrhotic livers had significantly increased levels of isoleucine, valine, succinate, lactate, and betaine [150]. Another NMR study was conducted on Chinese patients that included those with HCC.…”
Section: Fibrosis and Cirrhosismentioning
confidence: 99%